2018
DOI: 10.1002/bdd.2150
|View full text |Cite
|
Sign up to set email alerts
|

Transport mechanism of ursodeoxycholic acid in human placental BeWo cells

Abstract: Ursodeoxycholic acid (UDCA) is a first-line drug to treat intrahepatic cholestasis of pregnancy (ICP). However, its effects on the fetus are not clearly known. To better guide its clinical use, we aimed to study the mechanism underlying the placental transport of UDCA. The uptake and efflux of UDCA across placental apical membranes were studied using BeWo cells; effects of different exposure durations, UDCA concentrations, temperatures, and inhibitors of transporters were studied. A transwell assay was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 37 , 40 We did not quantify UDCA levels in the fetuses in the current study, but in vitro studies have shown that UDCA can be transported across the placenta bidirectionally. 41 It is therefore conceivable that UDCA treatment of the dams during gestation leads to elevated concentrations of UDCA in the circulation and livers of Cyp2c70 -/- fetuses.…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 40 We did not quantify UDCA levels in the fetuses in the current study, but in vitro studies have shown that UDCA can be transported across the placenta bidirectionally. 41 It is therefore conceivable that UDCA treatment of the dams during gestation leads to elevated concentrations of UDCA in the circulation and livers of Cyp2c70 -/- fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…This study sought to determine whether UDCA is transported by OATP4A1, which is known to utilize the placental glutamate gradient to transport TC (11,27). UDCA was found to be an inhibitor of OATP4A1 but did not transstimulate its activity, so it does not appear to be a substrate, as has been suggested by previous studies (28). Because OATP4A1 does not appear to transport UDCA, this raises the possibility that an unknown transporter or mechanism is implicated in the transfer of UDCA to the fetus.…”
Section: Discussionmentioning
confidence: 92%
“…At present, no effective treatment modalities are available for ICP, and the administration of ursodeoxycholic acid (UDCA) is a treatment option (Bicocca et al, 2018;Manna et al, 2019;Perez et al, 2006). The mechanism of action of UDCA is related to the displacement of hydrophobic bile acids to protect the hepatocyte membrane (Xia et al, 2018). Studies have reported that UDCA can relieve pruritus and decrease bile acid levels; however, whether it can prevent adverse effects on the fetus remains unproven (Chappell et al, 2019;Kumar and Kulkarni, 2020;Ovadia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%